The prime : prepare and repair your body for spontaneous weight loss - Chaudhary, Kulreet; Adamson, Eve (Harmony Books, 2016)
"Chaudhary discovered a beautiful side effect to the eating and lifestyle tools she gave her brain patients--shedding excess pounds. In this book, she shows readers that weight gain is a result of the body being in a toxic, inflammatory state. If your body is not prepared or 'primed' for weight loss, you will fight an uphill biochemical battle, and the odds of succeeding are slim. So she's reverse engineered our way of eating, so we can stop dieting backward and start succeeding instead. Using a blend of cutting-edge science and ancient wisdom, Dr. Chaudhary has crafted a plan like no other."--